Adsorption of oxytetracycline hydrochloride by magnetic activated carbon: kinetics, mechanism and site energy distribution analysis - Jia, Wenpeng; Sun, Lidong; Li, Huanjun; Lv, Tingjin; Tang, Yongzheng; Pi, Yongrui (Frontiers in Marine Science, 2025)
The remove of oxytetracycline hydrochloride (OTC) antibiotics from water presents both significant challenges and importance. In this study, magnetic activated carbon (MAC) was synthesized from powdered activated carbon and ferric compounds using an alkaline co-precipitation process. Various characterizations techniques employed to assess the microscopic morphology, pore structure, and surface functionality of the adsorbents. The maximum equilibrium adsorption (qm) of MAC for OTC at temperature of 20, 25, 30, 35, and 40°C were found to be 93, 112, 118, 108, and 117 mg/g, respectively, as determined by the Langmuir isotherm adsorption model. Thermodynamic and adsorption site energy analyses indicated that the adsorption process is a spontaneous endothermic reaction at elevated temperatures. During the OTC removal process, both chemisorption and physisorption mechanisms were observed, with adsorption site energies ranging from 4 to 16 kJ/mol, suggesting that chemical adsorption likely played a predominant role. The adsorbent material demonstrated excellent adsorption efficiency and a spontaneous nature, making it a promising candidate for the environmentally friendly treatment of antibiotic-contaminated wastewater.